(untitled) (Junior Management Science, 2017)
Bitcoin has emerged as a popular digital currency and arouses the interest not only of programmers, but also of investors and academics. What interests them most is its underlying technology, the blockchain. This thesis aims at giving an overview of the current state of cryptocurrencies and compares their different designs and approaches to Bitcoin. The blockchain technology will be explained, as well as how it could impact many aspects in life by showcasing different applications of Ethereum blockchain-based smart contracts. Based on the evaluation of the different cryptocurrencies and preceding conclusions, specific cryptocurrencies will be applied to the Tasklet system before proposing the implementation of the blockchain technology in such a system, in order to establish a reward system. The paper reviews a heterogeneous, scattered body of knowledge including academic literature, but also non-scientific sources due to the constantly evolving technology. On this basis, the advantages of Bitcoin, but also its weaknesses, as well as the vast potential of blockchain are discussed. Results indicate that although Bitcoin’s framework may be limited, it will still play an important role in the future due to its dominance in the cryptocurrency market. The short display of blockchain-fueled applications and its effects has shown its potential to transform the internet, leading to the rise of the Web 3.0.Keywords: Bitcoin, Blockchain, Cryptocurrency, Distributed Ledger Technology, Smart Contract